PENGARUH LEVERAGE, LIKUIDITAS, DAN PROFITABILITAS TERHADAP PENGUNGKAPAN LAPORAN KEUANGAN TAHUNAN PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2013-2016 - Wulandari, Tiara; Purwanto, Nanang; Setiyowati, Supami Wahyu (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2017)
This study aims to determine, test, and explain the effect of Leverage, Liquidity, and Profitability on Disclosure of Annual Financial Statements in Property Companies and Real Estate in Periods 2013-2016. This Study used quantitative approach, by testing classic assumptions, statistical analysis tools use multiple linear regression analysis. This study used secondary data types obtained through documentation techniques. Regression analysis used is multiple regression analysis and sampling techniques using a purposive sampling method, so 31 data samples from 49 Property and Real Estate Companies listed on the Indonesia Stock Exchange Period 2013-2016 were obtained. The results are conclude that partially and simultaneously or together leverage, liquidity, and profitability affect the disclosure of annual financial statements on the Property and Real Estate Companies listed on the Indonesia Stock Exchange Period 2013-2016.